Problem of delamination in RC beams strengthened by RRP with rheological model of adhesive leyer = Problem delaminacji w konstrukcjach żelbetowych wzmacnianych taśmami kompozytowymi z uwzględnieniem reologii kleju - Kula, Krzysztof; Socha, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper deals with one of the most dangerous failure modes in layered structures, namely delamination. The strengthening layer is modelled by a solid-shell finite element. The mechanical modelling of delamination onset and propagation is based upon a cohesive zone model implemented into a cohesive element located between adhesive layer and a concrete structure.
Keywords: delamination; FRP; concrete; cohesive element; solid-shell element; rheological model of epoxy; ABAQUS; CFRP; beton; stal; kompozyt; konstrukcje warstwowe; pełzanie; reologia; wzmacnianie